Transformation Of Human Ecology In Uzbekistan: Steps Toward Ecological Conscience - Bayeshanov Abdulla Mustafayevich (Periodica Journal, 2026)
This article analyzes the transformation of human–nature relations in Uzbekistan under contemporary ecological challenges. It examines the significance of ecological conscience in conditions of alienation from nature and highlights the role of human spirituality amid an ecological crisis. The study emphasizes that fostering ecological responsibility and ethical awareness is essential for overcoming environmental degradation and achieving sustainable development.
Keywords: alienation from nature; ecological conscience; transformation